Pengalaman dan Kehidupan Keseharian Penyandang Disabilitas di Kota Bandung - Ahadiyah, Dwina Nurul; Herawati, Erna (Universitas Muhammadiyah Sorong, 2024)
This study describes the experiences and daily lives of people with disabilities in the city of Bandung using qualitative phenomenological methods. The data collection technique was carried out through in-depth observation and interviews of people with physical disabilities, deaf, blind, and cerebral palsy who were recruited from various communities that shelter people with disabilities in the city of Bandung. The results of this study show that the daily life of people with disabilities is full of challenges. Every day they are faced with problems related to their physical condition and sociocultural problems due to this physical condition. Every step they take is their attempt to adapt to a situation that was not specifically designed for them. However, with various strategies, they managed to face every challenge. Experience after experience of people with disabilities in facing challenges and problems in daily life, as well as successful experiences in facing challenges have improved their life skills and made them more empowered and have a more meaningful life.